Consumer trust in social network sites in Vietnam: PLS-SEM-ANN analysis - Tien-Thao Cong Phan; Tri-Quan Dang; Luan-Thanh Nguyen (Proceedings of the National Conference in Education and Commerce, 2023)
While social network sites (SNSs) has emerged as one of the most promising futuristic trends in mobile commerce (m-commerce), how customers' trust impact on customer attitude and willingness to buy through SNSs remains largely underexplored. This study develops a theoretical model to examine the impacts of characteristics of trustees on customer's trust, customer attitude, and willingness to buy through theory of reasoned action (TRA). A survey was conducted and 200 valid questionnaires were collected from customers using Facebook, Twitter, and Tiktok platforms in Vietnam. Firstly, this study confirms that perceived reputation, multichannel integration, and system assurance exerted a positive influence on customer trust then customer trust has an influence on customer attitude and lead to willingness to buy. Secondly, the Neural Network Model was employed to rank relatively significant predictors obtained from structural equation modeling (SEM). This study contributes to the growing literature on the use of SNS apps in trying to elevate the m-commerce business. The new methodology and findings from this study will significantly contribute to the extant literature of m-commerce setting. Therefore, for practitioners concerned with fostering trust for their business when using SNS, the findings stress the importance of trust in m-commerce an integrated approach centered on key findings of this study.
Keywords: 330; m-commerce; Willingness to buy; TRA; Artificial neural network